Sharp vascular calcifications and acute balloon rupture during embolization. - Horton, J A; Jungreis, C A; Stratemeier, P H (American Journal of Neuroradiology, 1991)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf